2017
DOI: 10.1136/bjsports-2016-096915
|View full text |Cite
|
Sign up to set email alerts
|

Exercise prescription for overhead athletes with shoulder pathology: a systematic review with best evidence synthesis

Abstract: Objective To produce a best evidence synthesis of exercise prescription used when treating shoulder pathology in the overhead athlete. Design A systematic review of exercises used in overhead athletes including case studies and clinical commentaries. Data sources MEDLINE, PubMed, SPORTDiscus and CINAHL from database inception through July 8, 2016. Methods We examined data from randomised controlled trials and prospective cohort (level I-IV evidence) studies that addressed exercise intervention in the rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Strong consideration should be given to non-operative management options such as exercise interventions and/or data-based interval hitting programme 21. Wright et al ,22 reviewed the literature examining ‘exercise prescriptions’ for overhead athletes with shoulder pathology, demonstrating great variability though strong evidence to support the use of single-plane, open chain upper extremity exercises performed below 90 degrees of elevation and closed upper extremity exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Strong consideration should be given to non-operative management options such as exercise interventions and/or data-based interval hitting programme 21. Wright et al ,22 reviewed the literature examining ‘exercise prescriptions’ for overhead athletes with shoulder pathology, demonstrating great variability though strong evidence to support the use of single-plane, open chain upper extremity exercises performed below 90 degrees of elevation and closed upper extremity exercises.…”
Section: Discussionmentioning
confidence: 99%
“…These latest findings between the function of the lower extremity and dysfunction of the upper extremity reiterate the importance of the clinical awareness of the pathomechanics within the kinetic chain that can hinder overhead athlete performance and increase their risk of injury 3 . A most recent review of exercise prescription for overhead athletes with shoulder pathologies suggested that rehabilitation address all aspects of injury and recovery including exercises based on local, regional, and global approaches and exercises based on the specific athletic movement 23 . Because rehabilitation programs aim to address local and global stabilizers of the lumbopelvic-hip complex (LPHC), dynamic assessments for overhead athletes should focus on the LPHC.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of the rehabilitation for overhead athletes, authors 7 of a recent systematic review recommended single-plane open chain exercises below 908 of shoulder elevation, including elastic resistance. For optimal scapular muscle balance, adding an elastic resistance to external rotation during an elevation exercise has been proven beneficial as it increases middle (MT) and lower (LT) trapezius activity.…”
mentioning
confidence: 99%
“…For optimal scapular muscle balance, adding an elastic resistance to external rotation during an elevation exercise has been proven beneficial as it increases middle (MT) and lower (LT) trapezius activity. 8 Additionally, clinical experts advise incorporating the kinetic chain into shoulder rehabilitation exercises 7,9,10 because upper extremity performance does not depend on a single shoulder-joint movement but rather on sequenced activation of the lower to the upper kinetic chain. 2,3,7 Moreover, scapular muscle activity is influenced by incorporating the kinetic chain into shoulder exercis-es.…”
mentioning
confidence: 99%
See 1 more Smart Citation